Linking sedentary behavior and mental distress in higher education: a cross-sectional study - Subiron-Valera, Ana Belen; Rodriguez-Roca, Beatriz; Calatayud, Estela; Gomez-Soria, Isabel; Andrade-Gómez, Elena; Marcen-Roman, Yolanda (Frontiers in Psychology, 2023)
Background: Sedentary behaviour among university students could negatively affect their mental health. Objective: The aim of this study was to examine the relationship of mental health (anxiety and depression) and sedentary behaviour between gender in Health Degrees at the University of Zaragoza. Design: Cross-sectional descriptive study. Participants: Sample of 257 University students who completed an online questionnaire. Methods: Sedentary behaviour was assessed with the SBQ questionnaire. Anxiety and depression were assessed with the GADS questionnaire. The Mann-Whitney U test and multiple linear regression models were used. Results: In comparison to men, female students with symptoms of anxiety spend more time in total engaged in sedentary behaviours (10.56 ± 4.83) vs (7.8 ±3.28) (p <0.001) and mentally-passive sedentary activities (2.24 (1.57) vs 1.15 (0.90) (p <0.005). Female students at risk of depression also spend more hours engaged in mentally-passive sedentary behaviours in comparison to men (8.28 ± 50.70 vs 1.27 ± 1.02) (p=0.009). Conclusions: Female students at risk of anxiety and/or depression spend more time engaged in sedentary activities in comparison to male students. The risk of anxiety and depression is associated with the total number of hours a day spent engaged in sedentary behaviours and with mentally passive behaviours, but not mentally active behaviours.